2014
DOI: 10.1172/jci76375
|View full text |Cite
|
Sign up to set email alerts
|

Efferocytosis produces a prometastatic landscape during postpartum mammary gland involution

Abstract: qRT-PCR. Whole-tumor RNA was harvested with an RNeasy kit (QIAGEN), and cDNA was synthesized (High Capacity; Applied Biosystems) and amplified using the murine cDNA-specific primers (Integrated DNA Technologies) listed in Supplemental Methods, along with SYBR Green Supermix (Bio-Rad). The following primers were used: MRC1 (forward: 5′ CCCTCAGCAAGCGATGTGC 3′; reverse: 5′-GGATACTTGCCAGGT CCCCA-3′); iNOS (forward: 5′-GGAGCATCCCAAGTACGAGTGG-3′; reverse: 5′-CGGCC-CACTTCCTCCAG); IL10 (forward: 5′-GGCGCTGTCATC-GATTTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 71 publications
(93 reference statements)
4
147
0
1
Order By: Relevance
“…Furthermore, activation of Stat3 by efferocytosis mediates the M2-like polarization of bone marrow macrophages (12). In vivo studies in breast and colon cancer showed that efferocytosis induced M2 polarization and metastasis, while increased cell death correlated with poorer outcomes (13,48). Moreover, the proinflammatory cytokine IL-6 induced M2-like macrophage polarization in human macrophages (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, activation of Stat3 by efferocytosis mediates the M2-like polarization of bone marrow macrophages (12). In vivo studies in breast and colon cancer showed that efferocytosis induced M2 polarization and metastasis, while increased cell death correlated with poorer outcomes (13,48). Moreover, the proinflammatory cytokine IL-6 induced M2-like macrophage polarization in human macrophages (49).…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of apoptotic cancer cells (termed efferocytosis) is a process often underestimated during tumor progression due to rapid clearance by phagocytes (11). Tumor cell death, significantly amplified by chemotherapies or other targeted therapies, triggers extensive efferocytosis, which has been suggested to accelerate further tumor growth at least in part by inducing M2-like macrophage polarization and resultant protumoral functions (12,13).…”
Section: Proinflammatory Cytokines Are Induced In Macrophages Upon Apmentioning
confidence: 99%
“…Besides promoting tumour growth, apoptotic cells may also facilitate metastatic tumour progression 69 . It is well known that pregnancy reduces the overall risk of developing breast cancer; however when breast cancer is diagnosed in postpartum women it is often more aggressive and has a poorer prognosis compared to disease diagnosed in nulliparous women 70 .…”
Section: Apoptosis Cell Competition and Cancermentioning
confidence: 99%
“…Implicating the clearance of apoptotic cells in cancer progression, a recent study in an MMTV-PyMT mouse model of breast cancer found that a high level of efferocytosis in parous animals promoted TAM infiltration, stimulation of a wound-healing cytokine response and increased metastasis 69 .…”
Section: Apoptosis Cell Competition and Cancermentioning
confidence: 99%
“…Besides promoting tumour growth, apoptotic cells may also facilitate metastatic tumour progression. Furthermore, through massive cell death, leading to extensive efferocytosis (clearance of dead cells), promoted TAM infiltration, stimulation of a wound-healing cytokine response and increase in metastasis, implicate the clearance of apoptotic cells in cancer progression (Stanford et al 2014). Controlling of caspase activity is another important fact, as the level of caspase activity required to kill a cell is not so high (Rehm et al 2006).…”
Section: Apoptosismentioning
confidence: 99%